2022
DOI: 10.1016/j.jdin.2021.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Association between atopic dermatitis and COVID-19 infection: A case-control study in the All of Us research program

Abstract: Background There is incomplete understanding of the risk of coronavirus disease 2019 (COVID-19) infection in atopic dermatitis (AD) patients. Objective To evaluate the risk of COVID-19 infection in AD patients in a large, diverse cohort. Methods A case-control study of the All of Us cohort to analyze the association between AD and COVID-19. Comorbidities and risk factors were compared between cases and controls usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…AD, a form of eczema, is an allergic skin disease often related to asthma, food allergy, allergic conjunctivitis, and AR 29 . In observational studies, the relationship between AD and COVID-19 remained murkier: some studies [30][31][32] suggested that AD was associated with increased risk for COVID-19, while others suggested that it was associated with reduced risk [33][34][35] or had no effect 36 . Cohort studies have shown a reduced risk of SARS-CoV-2 infection in patients with AD treated with Dupilumab 35 .…”
Section: Discussionmentioning
confidence: 99%
“…AD, a form of eczema, is an allergic skin disease often related to asthma, food allergy, allergic conjunctivitis, and AR 29 . In observational studies, the relationship between AD and COVID-19 remained murkier: some studies [30][31][32] suggested that AD was associated with increased risk for COVID-19, while others suggested that it was associated with reduced risk [33][34][35] or had no effect 36 . Cohort studies have shown a reduced risk of SARS-CoV-2 infection in patients with AD treated with Dupilumab 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies did not demonstrate atopic dermatitis as a key independent risk factor to developing severe SARS-CoV-2 infection ( 5 7 ). However, more recent studies established that AD is associated with an increased odds of COVID-19 infection even after controlling for common comorbidities ( 8 , 9 ). A systematic review evaluating cutaneous manifestations in patients infected with COVID-19 have shown that 20% of these patients had an underlying dermatologic disease including atopic dermatitis ( 10 ).…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Atopic dermatitis is considered a Th2-balanced disease often associated with bronchial asthma, allergic rhinitis, allergic conjunctivitis, and food allergy [ 55 ]. Atopic dermatitis has been reported to be associated with an increased risk of COVID-19 in some research [ 56 , 57 , 58 ] and with decreased risk [ 59 , 60 , 61 ] or no difference in other studies [ 60 , 61 , 62 ].…”
Section: Inflammation Exacerbates Covid-19 Infectionmentioning
confidence: 99%